ARAHAN DAN MANAJEMEN PENGANGKUTAN SAMPAH DI KECAMATAN PONDOK GEDE KOTA BEKASI - Sodikin Sodikin (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
Garbage in Indonesia is still a difficult problem to solve, this occurs due to the amount of litter were increasingly grow in line with population growth. Sub Pondok Gede Bekasi City is located on the border with East Jakarta, has a large population growth is 3.48% / year this led to increasingly dense population density, which affects the volume of waste produced by the population every day. Based on the analysis, it is known that the volume of waste generated in the district population Pondok Gede in 2010 with a population of 235 579 inhabitants is 188 464 M3. After the projected population in 2025 will amount to be 358 551 inhabitants and the volume of waste would be increased to 322 696 M3. Direction and management of solid waste transportation is done by determining the number of polling stations and the number of trucks needed for all the rubbish served and can be transported. Based on the results of the analysis of the number of trucks required range of 2010 to 2005 ranged from 7 trucks to 11 trucks, TPS (temporary location) needed in 2010 was 524 units and in 2025 increased to 897unit. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i1.1410